The effects of oxidized temperatures on microstructures, electrical and gas sensing properties of tin oxide nano thin films - Hiếu, Nguyễn Văn; Hòa, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
Nano thin films of tin oxide are synthesized by sputtering for gas sensors application. The fabrication includes of deposition tin metal thin films on thermally oxidized SiO2 followed by thermal oxidation at 300oC, 400oC, 500oC and 600oC in air. The effect of oxidized temperatures on the morphologies; microstructure and gas sensing properties are investigated. Tin oxide tin films showed very high sensitivity to NOx at ppm level. The nano thin film oxidized at 400 oC showed highest sensitivity compared to others.